Moving beyond resilience education: musical counterstorytelling. (20th October 2019) - Hess, Juliet
ABSTRACT: Education discourse has recently turned toward resilience and grit. This article critiques the neoliberalism embedded in resilience education and the manner in which a resilience focus encourages docility, adaptation and vulnerability in youth in response to oppressive conditions rather than addressing oppression directly. As a site of resilience for marginalised youth, music is implicated in resilience education's failure to address systemic oppression. Drawing on Critical Race Theory (CRT), as a music educator, I challenge the tendency of resilience education to pathologise youth and individualise systemic issues and put forward songwriting within music education as a means to shift a pedagogy of vulnerability to a pedagogy of oppression that interrupts dominant narratives. I assert that a pedagogy of oppression through songwriting allows youth to create powerful musical counterstories that shift deficit discourse to focus on strengths.